Avaliação dos níveis plasmáticos da proteína Klotho em idosos com transtorno depressivo maior e sua relação com comprometimento cognitivo - Mariana de Souza Nicolau (2017)
Major depressive disorder (MDD) is one of the most common psychiatric diseases among the elderly. It is well-known that a number of clinical disorders are related to or intensified by MDD, which impacts their quality of life. Studies have shown that lower levels of Klotho are associated to age-related diseases, however little is known about its relation to MDD. For this reason, we decided to investigate the relation of Klotho protein with MDD in elderly people with and without mild cognitive impairment (MCI). Our hypothesis is that plasmatic Klotho protein levels are significantly reduced in elderly people with MDD and even lower in elderly people with MDD associated with MCI. In the present study we assessed 50 older adults from a psychogeriatrics outpatient service in Hospital das Clínicas Universidade Federal de Minas Gerais with ages between 60 and 86 (p=0.392) and 3 to 12 years of educational attainment (p=0.069), of these 17 were controls, 15 patients with MDD and 18 patients with MDD associated with MCI+MCI. Klotho plasmatic levels were measured by Immunoenzymatic assay (ELISA) sandwich. Our results show that Klotho levels are statistically lower in patients with MDD+MCI when compared to patients with MDD (p=0.0344) and controls (p=0.0418). Considering depressive episode subtype, the single episode TDM group presented statistically higher Klotho levels than the control group (p=0.0466). We also investigated whether depression onset would influence Klotho levels. The late onset MDD+MCI presented statistically lower Klotho levels in relation to the control group (p=0.0083) and in relation to the late onset MDD group (p=0.0175). The late onset TDM group presented significantly higher levels of Klotho when compared to the early onset MDD group (p=0.0239) and the control group (p=0.0083). Finally, we conducted correlation analyses and found that the MDD group and MDD+MCI group when analyzed together correlate with the tests used in the neuropsychological assessment. Our results show, for the first time, that plasma Klotho levels are lower in elderly people with MDD+MCI when compared to elderly people with MDD, especially regarding those with late onset MDD+MCI. Our findings show that Klotho is altered in single episode MDD in the elderly and when presenting lower levels, it may be a possible biomarker of MDD+MCI in the elderly.